2017
DOI: 10.1021/acssuschemeng.7b01108
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of High-Purity Cellulose Nanofibers from Wheat Straw through the Combined Environmentally Friendly Methods of Steam Explosion, Microwave-Assisted Hydrolysis, and Microfluidization

Abstract: High-purity cellulose nanofibers were isolated from wheat straw through an environmentally friendly, multistep treatment process that combined steam explosion, microwave-assisted hydrolysis, and microfluidization. The cellulose content of the processed nanofibers increased from 44.81% to 94.23%, whereas the hemicellulose and lignin contents significantly decreased. Scanning electron microscopy revealed the effects of the isolation treatments on fiber morphology and width. Atomic force microscopy was used to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(42 citation statements)
references
References 49 publications
6
34
1
1
Order By: Relevance
“…On the other hand, the crystallinity of the CNF obtained after proceeding to the second-stage bleaching was measured to be 57.1%, which was slightly lowered. This result is in good agreement with the results of Liu et al, which suggested that the crystallinity of CNF increased as the proportion of cellulose increases due to the removal of amorphous components such as lignin or hemicellulose during chemical bleaching step [52]. Figure 6b shows the FT-IR spectra of raw RH and RH fibers obtained by chemical bleaching for each stage.…”
Section: Optimization For the Synthesis Of Nano-structured Silica Witsupporting
confidence: 90%
“…On the other hand, the crystallinity of the CNF obtained after proceeding to the second-stage bleaching was measured to be 57.1%, which was slightly lowered. This result is in good agreement with the results of Liu et al, which suggested that the crystallinity of CNF increased as the proportion of cellulose increases due to the removal of amorphous components such as lignin or hemicellulose during chemical bleaching step [52]. Figure 6b shows the FT-IR spectra of raw RH and RH fibers obtained by chemical bleaching for each stage.…”
Section: Optimization For the Synthesis Of Nano-structured Silica Witsupporting
confidence: 90%
“…This connects well with the ATR-IR absorbance (* 1700 cm -1 ) band observed the in darker samples, which may be attributed to condensed tannins and humins and/or migration of lignin from the cell walls to the exterior surface. Thus, the absorbance band at approximately 1700 cm -1 may correspond to carbonyl stretching vibrations associated with ferulic and para-coumaric acid (Zhao et al 2011;Chandra et al 2016;Liu et al 2017). A similar effect of microwave processing temperature with respect to changes in functional groups for AH, either untreated (AH) or pretreated (AHET, AHHP), was noted.…”
Section: Atr-ir Analysismentioning
confidence: 72%
“…Microwaves have also been often combined with other treatments to produce nanocellulose. For instance, CNFs were extracted by steam explosion, microwave-assisted alkali treatment, and microfluidization, from wheat straw [ 72 ], or by microwave, high-shear homogenization and HPH, to valorize lime ( Citrus aurantifolia ) residues [ 73 ]. Likewise, sonication has also been associated with other processes.…”
Section: Eco-friendly Pickering Emulsionsmentioning
confidence: 99%